Modeling the Risk of Divorce in the Age Range of Marriage 1 – 10 Years using Weibull and Exponential Distributions - Desvina, Ari Pani; Marizal, Muhammad; Rahmi, Asra (Jurnal Sains Matematika dan Statistika, 2026)
Divorce is an act that is permitted in Islam but is hated by Allah. The rise in divorce over the last decade has become a serious concern for those involved in maintaining the resilience of household relationships. So, it is necessary to analyze at what age marriage becomes critical for maintaining it. This research uses divorce data from 2015 to 2020, with a variable measuring the maximum length of marriage at 10 years. The data used is secondary data obtained from the Pekanbaru Religious Court for 298 divorce cases. The analysis was carried out by determining the most appropriate distribution for modeling divorce data in Pekanbaru City: the Weibull or the Exponential distribution. This determination was carried out by a goodness-of-fit test using Akaike's Information Criterion (AIC) and Bayesian Information Criterion (BIC). The results show that the Weibull distribution is the most appropriate for modeling divorce data in Pekanbaru, with the highest divorce risk at a marriage age of around 42 months (3.5 years), with a probability of divorce of 14%.